Numerical Analysis of the Influence of Deep Foundation Pit Construction on Adjacent Subway Stations in Soft Soil Areas - Tao Yang; Shengyuan Xiong; Shuailei Liu; Yang Liu; Hao Zhao; Yanwei Li (Advances in Civil Engineering)
Deep foundation pit construction adjacent to a subway station in a soft soil area was numerically simulated with Midas GTS NX calculation software. The influence of the deep foundation pit construction on the deformation and stress of the subway station structure was studied, and the influence of the foundation pit retaining structure on the station was analyzed. The results show that during the foundation pit excavation process, the subway station slab rose as a whole and was greatly affected by the deformation of the common ground connecting wall, with the most unfavorable position changing as the excavation area changed. The excavation of foundation pits in different zones had a considerable influence on the east-to-west displacement of the common diaphragm wall outside the foundation pit. The maximum positive bending moment of the common diaphragm wall changed little, while the negative bending moment increased greatly during construction. Overall, the foundation pit excavation had a great impact on the negative moment of the common diaphragm wall. During the foundation pit excavation process, the subway station column lifted upward, and the maximum displacement, which was located at the west end of the station near the foundation pit, gradually weakened from west to east. As the foundation pit excavation process continued, the maximum axial force of the station column increased by 10.38%, and the pressure was the largest in the middle column. As the thickness of the diaphragm wall increased, the stiffness of the foundation pit retaining structure increased. After earthwork excavation and unloading, the locations in the retaining structure with high stiffnesses could resist deformations. The whole foundation pit was offset due to the high stiffness of the foundation pit retaining structure, which increased the horizontal deformation of the existing station structure. With increasing thickness, the relative horizontal deformation of the station slab gradually increased, mainly because the difference between the depths of the old and new diaphragm walls caused the embedded soil of the two same deep foundation pits to differ. Furthermore, there were great differences in the Earth pressure behind the wall. As the depth of the diaphragm wall increased, the active Earth pressure behind the diaphragm wall increased.